Metabolite Profiling of Macroalgae: Biosynthesis and Beneficial Biological Properties of Active Compounds - Carpena, María (2024)
Macroalgae are known as abundant sources of phytochemicals, which offer a plethora of beneficial biological properties. Besides being the most notable classes of compounds found in macroalgae, phlorotannins, bromophenols, and terpenoids comprise some of the most relevant for their biological properties. Phlorotannins, mainly prevalent in brown algae and structurally characterized as complex polyphenolic compounds derived from phloroglucinol units, possess robust antioxidant, anti-inflammatory, antitumor, and cytotoxic activities, modulated by factors such as the degree of polymerization and environmental conditions. Bromophenols, halogenated compounds found in algae and other marine organisms, exhibit significant antioxidant and antiviral properties. Their diverse structures and bromination patterns contribute to their potential as therapeutic and chemical defense agents. Pigments (chemically described as primary terpenoids) play a critical role in light absorption and energy transfer in macroalgae and are divided into three main groups: (i) carotenoids, which are primarily found in brown algae and provide photoprotective and antioxidant benefits; (ii) chlorophylls, known for facilitating the conversion of light into biological energy; and (iii) phycobilins, which are mostly found in red algae and play important roles in light absorption and energy transfer, besides providing remarkable health benefits. Finally, secondary terpenoids, which are particularly abundant in red algae (e.g., the Rhodomelaceae family) are central to cellular interactions and exhibit significant antioxidant, antimicrobial, antidiabetic, and anti-inflammatory properties. This study represents a detailed analysis of the biosynthesis, structural diversity, and biological activities of these macroalgae metabolites, emphasizing their potential biological properties.